Characterization of anaerobic ammonium oxidation (Anammox) bacteria from local wastewater treatment plant - Chandrasuriya, Lingam (Universiti Malaysia Sarawak (UNIMAS), 2011)
Anaerobic ammonium oxidation (anammox) process plays an important role in biological nitrogen removal. The bacteria catalyzing anammox process belongs to phylum Planctomycetales. The objective of this research is to characterize the anammox bacteria from leachate sample collected from a local wastewater treatment plant. Characterization of anammox bacteria includes enrichment, morphology, physico-chemical and molecular analysis. Screening for anammox bacteria was conducted using both enrichment culture and directly from leachate sample. Identification of anammox bacteria from enrichment culture and leachate sample using molecular method involves DNA extraction and PCR. Presence of anammox activity in enrichment culture was detected using physico-chemical method. No bands were obtained in peR using DNA extracted from enrichment culture. Presence of uncultured Planctomycete bacteria with potential anammox activity was detected through molecular analysis directly in leachate sample. Identification of anammox bacteria are advantageous as it can be applied in wastewater treatment plants to the level of ammonium and enhance the quality ofdischarged effluent.